(untitled) (Asian Journal of Medical and Biological Research, 2016)
Seeds of 15 hybrid rice varieties viz. Durber, Agomoni, Meghna, Hybrid super, Moyna, Tia, Gold, Aloron, Jagoron, Suborno, Safollo, Hira-1, Hira-2, Hira-4 and Hira-6 were collected from five different seed producing companies of Bangladesh. BAU-Biofungicide (3%), extracts of Garlic (1:1), Allamanda leaf (1:1) Bavistin (0.3%), Thiovit ( 0.3%) and Provax (0.3%) were used for treating seeds to improve quality of hybrid seeds of rice. The moisture content of seed samples ranged 12.20% to 14.37%, where highest moisture content was found in variety Meghna and lowest in variety Moyna. 1000-seed weight of seed samples ranged from 20.00 to 26.00g, where highest weight was recorded in Hira-4 and lowest was recorded both in Aloron and Hira-1. Seed health test revealed 11 different seed borne fungi viz. Bipolaris oryzae (0.0 to 25.5%), Fusarium moniliforme (0.00 to 3.0%), Fusarium oxysporum (0.0 to 18.0%), Aspergillus flavus (0.00 to 11.0%), Aspergillus niger (0.00 to 5.0%), Aspergillus candidus (0.00 to 15.0%), Penicillium spp. (0.0 to 7.0%) , Alternaria padwickii (0.0 to 1%), Alternaria tenuis (0.0 to 11.0%), Curvularia lunata (0.0 to 40.0%) and Nigrospora oryzae (0.0 to 4.0%) . Germination test resulted normal seedlings from 26.00 to 97.00%, where highest was recorded in variety Jagoron that treated with BAU-Biofungicide resulting highest increase in number of normal seedlings by 239.28% over untreated control. BAU-Biofungicide significantly decreased (upto 90.00%) formation of abnormal seedlings over untreated control. Moreover, BAU-Biofungicide increased up to 713.78% Vigor index over untreated control. Asian J. Med. Biol. Res. December 2015, 1(3): 406-415